(untitled) (Al-Farooq Journal of Sciences, 2026)
This research paper examines the role of partnerships between educational institutions and the urban sector in promoting the concept of "Green Education" as a modern approach to achieving urban sustainability. The study is premised on the hypothesis that Green Education is no longer merely a pedagogical trend confined within educational institutions; rather, it has evolved into an integrated system intrinsically linked to the city and to urban and environmental planning policies. The research problem is highlighted by the existence of a gap between the outputs of educational institutions and the requirements of sustainable urban planning, as well as the limited application of academic knowledge in addressing environmental and urban challenges within cities. The study aims to analyze the nature of these partnerships and explore their role in operationalizing Green Education, while proposing a practical framework applicable to developing cities. Employing a descriptive-analytical methodology, the study reviews relevant scientific literature and analyzes international models and case studies regarding "Green Universities" and sustainable cities. The objective is to derive a set of findings demonstrating that strengthening institutional partnerships can enhance the efficiency of urban planning and support the transition toward more sustainable and environmentally resilient cities. Furthermore, such partnerships contribute to integrating education with practical reality, thereby transforming universities into influential urban actors.